Osoba z głęboką intelektualną i wieloraką niepełnosprawnością podmiotem badań empirycznych – perspektywa badacza/badaczki - Kopeć , Danuta (Studia Edukacyjne, 2023)
Individuals with profound intellectual and multiple disabilities (PIMD) present considerable research challenges due to their psycho-physical condition and their functioning as research subjects. Using two research projects as examples, one Polish (Kopeć, 2013, The (Non)-educational Reality of Indivi- dual with Profound Intellectual Disabilities) and the other Finnish (Vehmas, Mietola, 2021, Narrowed Lives: Meaning, Moral Value, and Profound Intellectual Disability), difficulties encountered during research involving individuals with PIMD were identified. The challenges related to the methodology of the conducted research projects were discussed, such as the choice of research paradigm, selection of research method, and their execution. Attention was also drawn to concerns associated with obtaining informed consent from individuals with PIMD who are subjects of the study. Referring to the research projects conducted, the researchers presented their approach to resolving the difficulties encountered during the research process.